2014
DOI: 10.1186/1471-2431-14-159
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a reference dataset of neck sizes in children: standardizing a potential new tool for prediction of obesity-associated diseases?

Abstract: BackgroundNeck circumference (NC), is an emerging marker of obesity and associated disease risk, but is challenging to use as a screening tool in children, as age and sex standardized cutoffs have not been determined. A population-based sample of NC in Canadian children was collected, and age- and sex-specific reference curves for NC were developed.MethodsNC, waist circumference (WC), weight and height were measured on participants aged 6–17 years in cycle 2 of the Canadian Health Measures Survey. Quantile reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 21 publications
8
53
4
2
Order By: Relevance
“…The results of this study have shown that body weight and BMI have a positive correlation with NC, corroborating other studies conducted with children older than 2 years of age, in Brazil and other countries. 7,9,12,13,[15][16][17][18]20 The results of the present study also show that there was a moderate positive correlation between NC and BMI in both genders according to age group, supporting the results from studies conducted with Turkish, American and Chinese children. 7,12,18 However, some important limitations should be considered.…”
Section: Neck Circumference To Identify Excess Body Weight In Childresupporting
confidence: 80%
See 4 more Smart Citations
“…The results of this study have shown that body weight and BMI have a positive correlation with NC, corroborating other studies conducted with children older than 2 years of age, in Brazil and other countries. 7,9,12,13,[15][16][17][18]20 The results of the present study also show that there was a moderate positive correlation between NC and BMI in both genders according to age group, supporting the results from studies conducted with Turkish, American and Chinese children. 7,12,18 However, some important limitations should be considered.…”
Section: Neck Circumference To Identify Excess Body Weight In Childresupporting
confidence: 80%
“…The values for sensitivity were also high and similar to those of other studies that have investigated the use of NC as a measure to evaluate excess body weight in children and adolescents. 7,12,15,16,18 However, in the present study, specificity was lower than that found in other studies, 7,12,15,18,21 resulting in a higher number of false-positives, i.e., a high proportion of children classified as having excess body weight when in fact they did not.…”
Section: Neck Circumference To Identify Excess Body Weight In Childrecontrasting
confidence: 55%
See 3 more Smart Citations